Evaluation of pavement friction according to european standards - Jan Celko; Matus Kovac (Communications - Scientific letters of the University of Zilina, 2004)
Pavement friction was measured in Slovakia by SKIDDOMETER BV 11. An evaluation of skid resistance by Mu index value for use in the Slovak Pavement Management System (PMS) is based on one parameter of friction, only. The tendency to adapt the Slovak PMS to European standards involves creation of criteria for the skid resistance evaluation by International Friction Index IFI. The Slovak SKIDDOMETER BV11 did not participate in the PIARC harmonisation experiment for pavement friction measurement. Therefore the new approach for IFI calculation was required. The PIARC experiment and concerned equipment were analysed in detail. The British Portable Tester TRL was chosen as subsidiary equipment depending on Canadian experiences. The new methodology for IFI calculation by the Slovak SKIDDOMETER was suggested depending on comparison measurements and experiences analyses. On the base of new methodology criteria for pavement skid resistance evaluation were created.